2007
DOI: 10.7882/az.2007.014
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring populations of Heath FrogLitoria littlejohniin the Shoalhaven region on the south coast of New South Wales

Abstract: We monitored populations of the Heath Frog Litoria littlejohni in conservation reserves near Nowra on the south coast of New South Wales. Thirteen 250 m transects located along perennial creeks were surveyed at night once a year for 30 minutes each from 2001 to 2006. The sites covered a range of altitudes and vegetation communities and were surveyed between late August and October. The area has a relatively high population density of L. littlejohni, with animals being detected at 12 of the 13 sites. A period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…These variations in frog species richness at site level is consistent with other studies, identifying some increases (Brown et al 2011;Allingham and Harvey 2013;Grundel et al 2015;Mester et al 2015) but also decreases after fire (Cano and Leynaud 2010;Constible et al 2016). Such dichotomous responses occur in Australian frogs, with no discernible effects of fire detected for Heleioporus eyrei, Litoria olongburensis, L. freycineti or Crinia tinnula, but a negative impact was documented for both Litoria littlejohni (Daly and Craven 2007) and Geocrinia lutea (Driscoll and Roberts 1997).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These variations in frog species richness at site level is consistent with other studies, identifying some increases (Brown et al 2011;Allingham and Harvey 2013;Grundel et al 2015;Mester et al 2015) but also decreases after fire (Cano and Leynaud 2010;Constible et al 2016). Such dichotomous responses occur in Australian frogs, with no discernible effects of fire detected for Heleioporus eyrei, Litoria olongburensis, L. freycineti or Crinia tinnula, but a negative impact was documented for both Litoria littlejohni (Daly and Craven 2007) and Geocrinia lutea (Driscoll and Roberts 1997).…”
Section: Discussionsupporting
confidence: 89%
“…Some studies show frog species are not obviously affected by fire (Bamford 1992;Lowe et al 2013;, whereas others show some species experiencing population declines. For example, Litoria littlejohni (Daly and Craven 2007) and Geocrinia lutea (Driscoll and Roberts 1997) experienced declines, and one study even documented a local population extinction (Lemckert 2000). Despite the contributions of finer-scale or localised studies elucidating the effects of fire on Australian frogs, we lack evidence across larger spatial scales or for mega-fires, such as those experienced in 2019/ 2020, and those that are predicted to increase under future climate change (Lee et al 2022).…”
mentioning
confidence: 99%
“…Knowledge of frog responses to fire is particularly limited, and much is derived from studies on temperate pond‐breeding species in North America (Lowe, Castley, & Hero, 2013). Few studies exist on the impact of fire on Australian frogs, and these have typically indicated that frog species are relatively resilient to fires (Bamford, 1992; Daly & Craven, 2007; Driscoll & Roberts, 1997; Lowe et al, 2013; Potvin et al, 2017; Westgate, Driscoll, & Lindenmayer, 2012; Westgate, MacGregor, Scheele, Driscoll, & Lindenmayer, 2018). However, these studies consider relatively low‐intensity fires, a limited number of species and relatively small geographic areas.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of direct sunlight and the properties of rock to store and radiate heat and provide refuge sites (especially loose rock on rock) were considered significant biophysical components that catered for certain species of reptiles as has been demonstrated in rock outcrops further south in NSW (Pike et al 2011). This correlation between elevated reptile species richness with exposed rock outcrops has been noted for other regions in New South Wales (Daly 2004(Daly , 2006(Daly and 2007. Australian Zoologist volume 35 (4)…”
Section: Species Diversity and Densitymentioning
confidence: 90%
“…Surveys need to be conducted over a range of nights and in a range of seasons in order to detect all species present and to account for the influence of climatic conditions on detectability. Call playback and tadpole sampling are relatively recent methods used to detect rare species and habitat specialists (eg, Daly et al 2001, Daly et al 2002, Daly and Craven 2007. However, at the time of our surveys the use of such methods was rudimentary.…”
mentioning
confidence: 99%